(untitled) (Религиски дијалог и соработка, 2026)
This paper examines the evolution of tolerance from its mythological and philosophical roots in the ancient world to its contemporary role in interreligious and interethnic relations. It argues that the Balkans, far from being a perpetual zone of conflict, represent a microcosm of coexistence in which religious diversity has shaped identity, culture, and politics. Combining comparative historical analysis with empirical data collected among university students in North Macedonia, the study explores how religion continues to function as a fundamental marker of belonging even in secularized societies. Drawing on religious studies, sociology, and security theory, the paper analyzes the dual role of religion—as both a force for peace and an instrument of political mobilization—and identifies education and religious literacy as among the most sustainable paths toward peacebuilding and global security.